Five Tuesdays in winter [large type] - King, Lily (Thorndike Press large print core series., 2022)
"Told in the voices of characters of all ages, these tales explore desire and heartache, loss and discovery, jolting violence, and the inexorable tug toward love at all costs. A bookseller's unspoken love for his employee rises to the surface, a neglected teenage boy finds much-needed nurturing from an unlikely pair of college students, a girl's loss of innocence at the hand's of her employer's son becomes a catalyst for strength and confidence, and a proud nonagenarian rages helplessly in his granddaughter's hospital room. Romantic, hopeful, brutally raw, and unsparingly honest, these stories are, above all, about King's enduring subject of love"--